2008
DOI: 10.1093/carcin/bgn130
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Rad51 in cytotoxicity induced by epidermal growth factor receptor inhibitor (gefitinib, IressaR) and chemotherapeutic agents in human lung cancer cells

Abstract: Gefitinib (Iressa(R), ZD1839) is a selective epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor that blocks growth factor-mediated cell proliferation and extracellular signal-regulated kinases 1/2 (ERK1/2) signaling activation. Rad51 is an essential component of the homologous recombination repair pathway. High level of Rad51 expression has been reported in chemo- or radioresistant carcinomas. We hypothesized that gefitinib may enhance the effects of the alkylating agent cisplatin- or the antitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 65 publications
2
49
0
Order By: Relevance
“…EGFR is essential for PDAC initiation because its loss in genetically engineered mouse models prevents PDAC development (38)(39)(40). Another important feature of EGFR biology that holds clinical promise for RIT is the inhibition of the noncanonical direct EGFR nuclear translocation pathway (41), which increases repair of DNA DSBs (42)(43)(44)(45), the most lethal of DNA lesions induced by conventional anticancer treatments. We previously reported that EGFR-directed RIT inhibited DNA-PK phosphorylation, a critical protein involved in nonhomologous end joining pathway of DSBs, and caused the degradation of RAD51, a protein involved in HR repair, in models of aggressive breast cancer (16).…”
Section: Discussionmentioning
confidence: 99%
“…EGFR is essential for PDAC initiation because its loss in genetically engineered mouse models prevents PDAC development (38)(39)(40). Another important feature of EGFR biology that holds clinical promise for RIT is the inhibition of the noncanonical direct EGFR nuclear translocation pathway (41), which increases repair of DNA DSBs (42)(43)(44)(45), the most lethal of DNA lesions induced by conventional anticancer treatments. We previously reported that EGFR-directed RIT inhibited DNA-PK phosphorylation, a critical protein involved in nonhomologous end joining pathway of DSBs, and caused the degradation of RAD51, a protein involved in HR repair, in models of aggressive breast cancer (16).…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer, high expression of Rad51 in tumor tissue is associated with an unfavorable prognosis (24). Our recent study has shown that the polycyclic hydrocarbon carcinogen benzo(a)pyrene can enhance the expression of Rad51 through the activation of ERK1/2 (45), and MEK1/2-ERK1/2 is the upstream signaling pathway to regulate the Rad51 expression, which is associated with the resistance to gefitinib, mitomycin C, and cisplatin in NSCLC (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer, high expression of Rad51 in tumor tissue is associated with an unfavorable prognosis (24). Our recent study has shown that the MEK1/2-ERK1/2 is the upstream signaling pathway in regulating the Rad51 expression (25,26). However, the role of Rad51 in regulating the response to erlotinib in different cell types of human NSCLC also remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…After the different treatments, the cells were rinsed twice with ice-cold phosphate-buffered saline and lysed in whole-cell extraction buffer [20 mM HEPES, pH 7.6, 75 mM NaCl, 2.5 mM MgCl 2 , 0.1 mM EDTA, 0.1% Triton X-100, 0.1 mM Na 3 VO 4 , 50 mM NaF, 1 g/ml leupeptin, 1 g/ml aprotinin, 1 g/ml pepstatin, and 1 mM 4-(2-aminoethyl)benzenesulfonyl fluoride]. Equal amounts of protein from each set of experiments were subjected to Western blot analysis as described previously (Ko et al, 2008a). The relative protein blot intensities were determined using a computing densitometer equipped with the ImageQuant analysis program (GE Healthcare, Chalfont St. Giles, Buckinghamshire, UK).…”
Section: Methodsmentioning
confidence: 99%
“…3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium (MTT; Sigma-Aldrich) assays were used to evaluate the inhibitory effects of emodin and MMC on cell viability as described previously (Ko et al, 2008a). In brief, cells were seeded on 96-well plates with RPMI containing 10% fetal calf serum in a final volume of 0.2 ml, incubated for 18 h, and then treated with the drugs for 24 h. After drug treatment, the MTT solution was added to each well and incubated for 3 h before the medium was removed.…”
Section: Methodsmentioning
confidence: 99%